Effectiveness and quality of mobile applications for pregnancy monitoring: A systematic review - restu pangestuti; Adi Heru Sutomo; Prima Dhewi Ratrikaningtyas (Placentum)
Technology is now increasingly developed and widely used in the world of health. This condition triggers the use of mobile applications for monitoring the health of pregnant women. However, the effectiveness of using applications for pregnancy monitoring still needs to be studied more deeply. This article is a literature study on the use of mobile applications for pregnancy monitoring. This systematic review aims to identify research published from January 2011 to December 2024 by searching in four databases (PubMed, Science Direct, Scopus, ProQuest). The included study addresses the effectiveness and quality of the use of mobile apps for health monitoring of pregnant women and this study is the primary study. Data extraction was carried out by 3 researchers with screening and discussion methods.A total of 3130 articles have been screened, 8 articles are included in the inclusion criteria. A total of 7 articles were randomized controlled trials and only 1 article was a quasi-experiment. The grouping category is 4, namely 2 articles providing health information, 1 article discussing pregnancy counseling, 2 articles discussing decision making and mental support, and three articles discussing pregnancy management. Mobile applications for pregnancy monitoring have an effective function in four categories of use, namely provide health information, pregnancy counseling, decision-making and mental support, and pregnancy care managementTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//